Rückblick auf 25 Jahre PROKLA - Lorek, Volker (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
The article focuses on the developmentof the PROKLA from 1970 to 1995. lt highlights some of the most impmtant articles and debates in view of the historic and academic circumstances in which they took place.